An investigation of modern building equipment technology adoption in the Australian construction industry. Issue 8 (17th September 2018) - Sepasgozar, Samad M.E.; Davis, Steven; Loosemore, Martin; Bernold, Leonhard
Abstract : Purpose: Research into the construction industry's adoption of modern equipment technologies, such as remote-controlled trucks, excavators and drones, has been neglected in comparison to the significant body of research into the adoption of information technology in construction. Construction research has also neglected to adequately consider the important role of vendors in the innovation diffusion process, focussing mostly on the role of the customer. Set within the context of Australia's construction industry, the purpose of this paper is to address these gaps in knowledge by exploring the role of customers and vendors in the diffusion of modern equipment technologies into the construction industry. Design/methodology/approach: Using contemporary models of innovation diffusion which move beyond the simple dualistic problem of whether innovation is supply-pushed or demand-pulled, 19 semi-structured interviews were undertaken with customers and vendors involved in two major modern equipment technology trade exhibitions in Australia. This was followed by the collection of documentary data in the form of photos, directory books, marketing material, catalogues, websites and booth and exhibition layouts to validate the proposed model and provide insights into vendor marketing strategies. These data were analysed using both content analysis and principal component analysis (PCA). Findings: According to the PCA and content analysis, vendor's engagement in the adoption of modern equipment technologies falls into three stages that correspond to three stages in the customer's adoption process. In the first stage, customers identify possible solutions and recognise new technologies following a previous recognition of a need. Vendors provide facilities for attracting potential customers and letting customers know that their technology exists and can help solve the customer's problem. The second stage involves customers gaining knowledge about the details of the new technology, and vendors focusing on detailed knowledge transfer through written materials and demonstrations of the functionality of the new technology. In the third stage, customers have specific questions that they want answered to assist them in comparing different vendors and solutions. By this stage, vendors have built a close relationship with the customer and in contrast to earlier stages engage in two-way communication to help the customer's decision process by addressing specific technical and support-related questions. Originality/value: The originality and value of this research is in addressing the lack of research in modern equipment technology adoption for building construction and the lack of data on the role of vendors in the process by developing a new empirical framework which describes the stages in the process and the ways that customers and vendors interact at each stage. The results indicate that conceptually, as the construction industry becomes more industrialised, current models of innovation adoption will need to develop to reflect this growing technological complexity and recognise that vendors and customers engage differently in the adoption process, according to the type of technology they wish to adopt.